Sources and levels of nitrogen and onion yield in the submedio São Francisco region - de Faria, Clementino M. B; Pereira, José Ribamar (Pesquisa Agropecuaria Brasileira, 1992)
Two experiments were carried out with onion crop (Allium cepa L.) under irrigation in 1987 and 1988, in Petrolina, PE, Brazil, in a Red-Yellow Latosol, with 10% of clay, 85% of sand, 0,6% of organic matter, and pH 6.5, with the objectives of evaluating new sources of N and obtaining an optimum level of this element in fertilizations. A randomized complete block design with a factorial arrangement was used, having three levels (40, 80 and 120 kg/ha of N) and three sources of N (urea, urea compacted with gypsum and "nitrossulfocalcium"), with two additional treatments (control and urea + gypsum), replicated four times. The onion crop showed a positive and significant response to N application. In 1987, urea compacted with gypsum contributed to a yield significantly superior in 35% to that obtained with only urea, whereas in 1988, there was no significant difference among N sources. In 1987, the N level which gave the maximum expected yield (29.58 t/ha) was 114 kg/ha, and in 1988 the maximum expected yield (54.31 t/ha) was achieved with 119 kg/ha of N. The average economic level of N was 115 ± 2.7 kg/ha.